Phosphate positive electrode material and preparation method and application thereof
By using flocculent carbon cladding layer and hydrothermal reaction combined with two-stage sintering treatment in lithium manganese iron phosphate positive electrode material, the low compaction density and low conductivity of the materials in the prior art are solved, and high Properties of lithium manganese iron phosphate positive electrode material.
Patent Information
- Application Number
- CN202411550902.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to realize lithium manganese iron phosphate positive electrode material with high compaction density and high rate performance, which has low conductivity and conductivity problems, and small particles and high carbon content lead to low compaction density.
The positive electrode material including a phosphate-based core and a carbon cladding layer is used. The carbon cladding layer is prepared from floc carbon material. It is formed by hydrothermal reaction and two-stage sintering treatment to form a high compaction density and high conductivity material.
It achieves high compaction density, large volume specific capacity, meets the requirements of high magnification, high stability and high conductivity, and improves the overall performance of the material.
Smart Images

Figure CN119480965A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of lithium-ion batteries, and in particular relates to a phosphate-based positive electrode material and a preparation method and application thereof. Background Art
[0002] As competition in the lithium battery industry continues to intensify and gradually enters a cycle of overcapacity, the development focus of the lithium battery industry chain is mainly on internal product upgrades + external collaborative cost reduction, that is, reducing costs and improving product performance. The cost of positive electrode materials is also relatively high, accounting for about 30-40% of the cost of lithium-ion battery materials. At the same time, the performance of lithium battery positive electrode materials is the decisive factor in the electrochemical performance of lithium-ion batteries, directly affecting the performance of the battery, and plays a leading role in the energy density and safety performance of the battery. At present, the most studied positive electrode materials are LiCoO2, LiNiO2, LiMn2O4, LiFePO4 and LiMnFePO4 (lithium manganese iron phosphate). Among them, lithium manganese iron phosphate is a solid solution of lithium iron phosphate and lithium manganese phosphate. The manganese element increases the voltage platform (close to the upper limit of the commercial electrolyte voltage of 4.3V), thereby increasing the energy density of the material. Compared with lithium iron phosphate, the energy density and low-temperature performance have been improved. Compared with the ternary positive electrode, lithium manganese iron phosphate inherits the high safety performance, low cost advantages and longer cycle life of phosphate-based positive electrode materials. In summary, the energy density of lithium manganese iron phosphate positive electrode material is 15-20% higher than that of lithium iron phosphate, driving the cost of battery products to drop by 5-10%.
[0003] However, the real large-scale application of lithium iron manganese phosphate still needs to overcome two major technical difficulties: 1) low conductivity and conductance problems (poor rate performance); 2) smaller particles and higher carbon content (low compaction density). Generally speaking, the compaction density of the positive electrode material is closely related to the battery capacity, efficiency, internal resistance and battery cycle performance, so the compaction density is also regarded as one of the reference indicators of the material energy density. The particles of lithium iron manganese phosphate are generally smaller than lithium iron phosphate, and the large number of gaps between small particles causes the compaction density of lithium iron manganese phosphate to be much smaller than that of lithium iron phosphate. Filling the gaps between particles can effectively increase its compaction density to close to the true density, that is, using the method of large and small particle grading to change the particle size distribution of the powder. However, this method requires the introduction of large particles, which reduces the rate performance of the material. At the same time, it is also difficult to achieve particle size grading. When the particle sizes of large and small particles are not compatible or the particle distribution is uneven, the bulk density will be reduced and the material consistency will be poor.
[0004] Therefore, there is an urgent need for a lithium iron manganese phosphate positive electrode material with high compaction density and high rate performance to solve the problem of increasing the compaction density and reducing the rate or increasing the rate and reducing the compaction density of lithium iron manganese phosphate in the prior art. Summary of the invention
[0005] The purpose of the present application is to provide a phosphate-based positive electrode material and a preparation method and application thereof, aiming to solve the problem in the prior art that it is impossible to obtain a phosphate-based positive electrode material with both high compaction density and high rate performance.
[0006] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:
[0007] In a first aspect, the present application provides a phosphate-based positive electrode material, comprising a phosphate-based core and a carbon coating layer, wherein the carbon coating layer comprises a flocculent carbon coating layer, and the flocculent carbon coating layer is prepared from a chelated organic carbon material.
[0008] In some embodiments, the phosphate-based cathode material is composed of micron secondary particles formed by agglomeration of several spherical nano primary particles, wherein the particle size of the primary particles is 200 to 400 nm, and the particle size of the secondary particles is 50 >5μm.
[0009] In some embodiments, the carbon coating layer includes a flocculent carbon coating layer and a normal carbon layer.
[0010] In some embodiments, taking the total mass of the phosphate-based positive electrode material as 100%, the carbon content in the phosphate-based positive electrode material is 1.2% to 1.4%.
[0011] In some embodiments, the chemical formula of the phosphate core is LiM a Fe b Mn c PO4, wherein 0≤a≤0.05, 0.2≤b≤0.8, 0.2≤c≤0.8, and a+b+c=1; M is selected from at least one of Ti, Mg, V, Ni, Nb, Co, La, Sc, and Ce.
[0012] In a second aspect, the present application provides a method for preparing a phosphate-based positive electrode material, comprising the following steps:
[0013] S01. The lithium source, iron source, manganese source, phosphorus source, M source and chelated organic carbon material are mixed for hydrothermal reaction, and then post-processed to obtain a precursor powder;
[0014] S02. The precursor powder is subjected to a two-stage sintering treatment to obtain a phosphate-based positive electrode material.
[0015] In some embodiments, the hydrothermal reaction is carried out at a temperature of 150 to 200° C. and for a time of 6 to 24 hours.
[0016] In some embodiments, the post-treatment includes: cooling the mixture obtained by the hydrothermal reaction, filtering to obtain a precipitate, and sequentially washing, drying and grinding.
[0017] In some embodiments, the step of subjecting the precursor powder to a two-stage sintering treatment includes: heating the temperature from room temperature to 300-450°C at a heating rate of 2-15°C / min, maintaining for 3-6 hours, performing a first sintering treatment on the precursor powder, and then heating the temperature to 550-750°C at a heating rate of 2-15°C / min, maintaining for 4-8 hours, and performing a second sintering treatment.
[0018] In some embodiments, after the first sintering process of the two-stage sintering process, a supplementary carbon material is added, and then the second sintering process of the two-stage sintering process is performed.
[0019] In some embodiments, the molar ratio of the lithium source, iron source, manganese source, phosphorus source, and M source is 1.00-1.02: 0.2-0.5: 0.2-0.5: 1: 0-0.2.
[0020] In some embodiments, the total mass of the raw material is 100wt%, and the added amount of the chelated organic carbon material is 0.1wt% to 10wt%.
[0021] In some embodiments, the M source includes an oxide containing at least one element of Ti, Mg, V, Ni, Nb, Co, La, Sc, and Ce.
[0022] In some embodiments, the chelated organic carbon material includes at least one of diethanolamine, ethylenediaminetetraacetic acid, sodium gluconate, tartaric acid, and polyacrylic acid.
[0023] In some embodiments, the lithium source includes at least one of Li2CO3, LiH2PO4, LiOH·H2O, CH3COOLi, and LiNO3.
[0024] In some embodiments, the iron source includes at least one of Fe(NO3)3, Fe2O3, and FeSO4·7H2O.
[0025] In some embodiments, the manganese source includes at least one of Mn(NO3)3, Mn2O3, and MnSO4·7H2O.
[0026] In some embodiments, the phosphorus source includes at least one of (NH4)3PO4, NH4H2PO4, LiH2PO4, and H3PO4.
[0027] In a third aspect, the present application provides a positive electrode plate, which includes a current collector and a positive electrode active layer formed on the surface of the current collector, and the positive electrode active layer includes a phosphate-based positive electrode material or a phosphate-based positive electrode material prepared by a method for preparing a phosphate-based positive electrode material.
[0028] In a fourth aspect, the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is selected from positive electrode sheets.
[0029] The first aspect of the present application provides a phosphate-based positive electrode material, which includes a phosphate-based core and a carbon coating layer, wherein the provided carbon coating layer includes a flocculent carbon coating layer, which can reduce the resistivity and avoid the risk of fusion and growth into large particles during high-temperature sintering, wherein the flocculent carbon coating layer is prepared from a chelated organic carbon material, which can also anchor various metals during the preparation process to avoid the generation of impurities, thereby ensuring the formation of highly crystallized, neatly shaped, uniform nano-sized grains, and the nano-scale particles are tightly agglomerated, which is beneficial to improving the overall compaction density of the material, and the carbon material can form a conductive network to improve the overall electronic conductivity of the material. Therefore, the obtained phosphate-based positive electrode material has a high compaction density and a large volumetric capacity, while meeting the requirements of high rate, high stability and high conductivity.
[0030] The second aspect of the present application provides a method for preparing a phosphate-based positive electrode material, wherein the preparation method first chemically bonds a lithium source, an iron source, a manganese source, a phosphorus source, an M source, and a chelated organic carbon material and undergoes a hydrothermal reaction to form a stable "metal-organic carbon" precursor powder, thereby achieving in-situ growth of a carbon layer on the surface of the phosphate-based positive electrode material grains and separation of grains during subsequent sintering; and then performing a two-stage sintering treatment, through two sinterings under different conditions, the various raw materials can be synergistically reacted to obtain spherical secondary particles of phosphate-based positive electrode materials. The prepared phosphate-based positive electrode material has a high compaction density and conductivity, and the preparation method is unique and effective, does not require the use of large-scale instruments and equipment, is easy to operate, and is suitable for a wide range of applications.
[0031] The positive electrode plate provided in the third aspect of the present application has a positive electrode active layer comprising the above-mentioned phosphate-based positive electrode material with high conductivity and high compaction density. Therefore, the obtained positive electrode plate has high rate performance and can be widely used in various types of secondary batteries.
[0032] The secondary battery provided in the fourth aspect of the present application includes the above-mentioned positive electrode plate with high rate performance. Therefore, the obtained secondary battery has high cycle efficiency and high charge and discharge specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0034] Figure 1 These are SEM images at different magnifications of the lithium manganese iron phosphate positive electrode material provided in Example 1 of the present application.
[0035] Figure 2 These are SEM images at different magnifications of the lithium manganese iron phosphate positive electrode material provided in Comparative Example 1 of the present application.
[0036] Figure 3 These are SEM images of the lithium manganese iron phosphate positive electrode material provided in Comparative Example 2 of the present application at different magnifications. DETAILED DESCRIPTION
[0037] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0038] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0039] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0040] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0041] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0042] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0043] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0044] A first aspect of an embodiment of the present application provides a phosphate-based positive electrode material, comprising a phosphate-based core and a carbon coating layer, wherein the carbon coating layer comprises a flocculent carbon coating layer, and the flocculent carbon coating layer is prepared from a chelated organic carbon material.
[0045] The first aspect of the embodiment of the present application provides a phosphate-based positive electrode material, which includes a phosphate-based core and a carbon coating layer, wherein the provided carbon coating layer includes a flocculent carbon coating layer, which can reduce the resistivity and avoid the risk of fusion and growth into large particles during high-temperature sintering, wherein the flocculent carbon coating layer is prepared from a chelated organic carbon material, which can also anchor various metals during the preparation process to avoid the generation of impurities, thereby ensuring the formation of highly crystallized, neatly shaped, uniform nano-sized grains, and the nano-scale particles are tightly agglomerated, which is beneficial to improving the overall compaction density of the material, and the carbon material can form a conductive network to improve the overall electronic conductivity of the material. Therefore, the obtained phosphate-based positive electrode material has a high compaction density and a large volumetric capacity, while meeting the requirements of high rate, high stability and high conductivity.
[0046] In some embodiments, the phosphate-based positive electrode material is a micron secondary particle formed by the agglomeration of several types of spherical nano primary particles. The primary particles are spherical particles with regular morphology, which is conducive to improving the processing performance of the material and ensuring the safety of downstream battery cell manufacturing; it is also conducive to the deintercalation of lithium in the lithium-ion positive electrode material, ensuring the rate performance of large-particle materials; and the absence of excess gaps between nano-scale particles is conducive to improving the compaction density of lithium manganese iron phosphate materials and ensuring the overall conductivity of the material. The positive electrode material of the agglomerated micron-scale secondary particles overcomes the shortcomings of the phosphate-based positive electrode material itself, such as low compaction, low electronic conductivity, and the large electrochemical side reaction contact surface of the nanoparticles themselves, so that the obtained phosphate-based positive electrode material takes into account the high-rate electrochemical performance of nano-scale lithium manganese iron phosphate and the high compaction density value of micron-scale large particles.
[0047] In some embodiments, the particle size of the primary particles is 200 to 400 nm. If the particle size of the primary particles is too large, it is not easy to form tightly bound secondary particles, which will affect the compaction density of the overall material; if the particle size of the primary particles is too small, the secondary particles obtained will easily lead to poor wettability of the electrolyte and weak processing performance in the subsequent battery preparation process. In some specific embodiments, the particle size of the primary particles includes but is not limited to 200nm, 220nm, 250nm, 280nm, 300nm, 320nm, 350nm, 380nm, 400nm and other typical but non-restrictive arbitrary point values or interval values between any two point values.
[0048] In some embodiments, the particle size D of the secondary particles 50 >5μm. The obtained secondary particles are micron-sized grains with a high compaction density.
[0049] In some embodiments, the compaction density of the phosphate-based cathode material is 2.20 to 2.50 g / cm 3 In some specific embodiments, the compaction density of the phosphate-based cathode material includes but is not limited to 2.20 g / cm 3 , 2.25g / cm 3 , 2.30g / cm 3 , 2.35g / cm 3 , 2.40g / cm 3 , 2.45g / cm 3 , 2.5g / cm 3 Typical but non-limiting arbitrary point values or interval values between any two point values.
[0050] In some embodiments, the total mass of the phosphate-based positive electrode material is 100%, and the carbon content in the phosphate-based positive electrode material is 1.2% to 1.4%. The carbon content in the phosphate-based positive electrode material is controlled to be moderate. If the carbon content is too high, the carbon content of the product after subsequent sintering treatment will be too high, and too many small particles will be sintered, affecting the properties of the material; if the carbon content is too low, the flocculent carbon coating layer cannot be formed, resulting in a too large particle size of the finished product particles, affecting the overall compaction density of the material.
[0051] In some specific embodiments, taking the total mass of the phosphate-based positive electrode material as 100%, the carbon content in the phosphate-based positive electrode material includes but is not limited to 1.2%, 1.25%, 1.3%, 1.35%, 1.4%, and other typical but non-limiting arbitrary point values or interval values between any two point values.
[0052] In some embodiments, the chemical formula of the phosphate core is LiM a Fe b Mn c PO4, wherein 0≤a≤0.05, 0.2≤b≤0.8, 0.2≤c≤0.8, and a+b+c=1; M is selected from at least one of Ti, Mg, V, Ni, Nb, Co, La, Sc, and Ce. A second aspect of an embodiment of the present application provides a method for preparing a phosphate-based positive electrode material, comprising the following steps:
[0053] S01. The lithium source, iron source, manganese source, phosphorus source, M source and chelated organic carbon material are mixed for hydrothermal reaction, and then post-processed to obtain a precursor powder;
[0054] S02. The precursor powder is subjected to a two-stage sintering treatment to obtain a phosphate-based positive electrode material.
[0055] The second aspect of the embodiment of the present application provides a method for preparing a phosphate-based positive electrode material. The method first chemically bonds a lithium source, an iron source, a manganese source, a phosphorus source, an M source, and a chelated organic carbon material and forms a stable "metal-organic carbon" precursor powder through a hydrothermal reaction, thereby realizing the in-situ growth of a carbon layer on the surface of the phosphate-based positive electrode material grains and the separation of grains during the subsequent sintering process; and then performing a two-stage sintering treatment. Through two sinterings under different conditions, the raw materials can be synergistically acted to obtain spherical secondary particles of phosphate-based positive electrode materials. The prepared phosphate-based positive electrode material has a high compaction density and conductivity, and the preparation method is unique and effective, does not require the use of large-scale instruments and equipment, is easy to operate, and is suitable for wide application.
[0056] In step S01, a lithium source, an iron source, a manganese source, a phosphorus source, an M source and a chelated organic carbon material are mixed for hydrothermal reaction, and then post-processed to obtain a precursor powder. In some embodiments, the molar ratio of the lithium source, the iron source, the manganese source, the phosphorus source, and the M source is 1.00-1.02: 0.2-0.5: 0.2-0.5: 1: 0-0.2.
[0057] In some embodiments, the lithium source includes at least one of Li2CO3, LiH2PO4, LiOH·H2O, CH3COOLi, and LiNO3.
[0058] In some embodiments, the iron source includes at least one of Fe(NO3)3, Fe2O3, and FeSO4·7H2O.
[0059] In some embodiments, the manganese source includes at least one of Mn(NO3)3, Mn2O3, and MnSO4·7H2O.
[0060] In some embodiments, the phosphorus source includes at least one of (NH4)3PO4, NH4H2PO4, LiH2PO4, and H3PO4.
[0061] In some embodiments, the M source includes an oxide containing any one of Ti, Mg, V, Ni, Nb, Co, La, Sc, and Ce.
[0062] In some embodiments, the total mass of the raw material is 100wt%, and the mass of the chelated organic carbon material added is 0.1wt% to 10wt%. In some specific embodiments, the total mass of the raw material is 100wt%, and the mass of the chelated organic carbon material includes but is not limited to 0.1wt%, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, and other typical but non-limiting arbitrary point values or interval values between any two point values.
[0063] In some embodiments, the chelated organic carbon material includes at least one of diethanolamine, ethylenediaminetetraacetic acid, sodium gluconate, tartaric acid, and polyacrylic acid.
[0064] Among them, the use of hydrothermal reaction can ensure that there is enough time for the metal and the chelated organic carbon material to form a stable "metal-organic carbon" complex, and ensure that the chelated organic carbon material can form a chelate with the iron source and manganese source in the solution, play a role in dispersing and fixing metal ions, avoid the formation of impurities in the subsequent high-temperature roasting of the material, and ensure the formation of highly crystalline uniform grains; and the chelated organic carbon material is mixed into the metal raw material in situ, realizing the in-situ growth of the carbon layer on the surface of the grain and the separation of the grains during the subsequent sintering process, which helps to form large micron-sized agglomerated particles. At the same time, the organic carbon source added in situ forms an in-situ coated carbon layer, which increases the contact area between the positive electrode material and the electrolyte, and alleviates the potential problem of poor wettability of the agglomerated large particles to the electrolyte. The hydrothermal reaction is different from the coprecipitation reaction. The coprecipitation reaction is to separate the precipitate after the solid is quickly formed. In the product obtained by the coprecipitation reaction, the metal cannot be firmly anchored to the organic carbon, so the carbon material will be destroyed during the subsequent sintering process, and the morphology and particle size of the obtained product will be affected.
[0065] Among them, when the amount of chelated organic carbon added is sufficient, when it is reacted as a carbon source, not only a flocculent carbon coating layer can be obtained, but also an in-situ coated carbon layer can be obtained; when the amount of chelated organic carbon added is too little, when it is reacted as a carbon source, a flocculent carbon coating layer can be obtained, then other carbon sources need to be added during the sintering reaction.
[0066] In some embodiments, the temperature of the hydrothermal reaction is 150-200°C, and the time is 6-24 hours. In some specific embodiments, the temperature of the hydrothermal reaction includes but is not limited to 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, and other typical but non-limiting arbitrary point values or interval values between any two point values. In some specific embodiments, the time of the hydrothermal reaction includes but is not limited to 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, 24 hours, and other typical but non-limiting arbitrary point values or interval values between any two point values.
[0067] Further, post-treatment is performed to obtain precursor powder.
[0068] In some embodiments, the post-treatment includes: cooling the mixture obtained by the hydrothermal reaction, filtering to obtain a precipitate, and sequentially washing, drying and grinding.
[0069] In some specific embodiments, the lithium source, iron source, manganese source, phosphorus source, M source and chelated organic carbon material are mixed to obtain a mixed solution, the mixed solution is transferred to a 50 mL stainless steel hydrothermal autoclave with polytetrafluoroethylene, the hydrothermal autoclave is sealed and transferred to a blast drying oven with a set temperature for hydrothermal reaction, after the reaction is completed, it is naturally cooled to room temperature for suction filtration, washed with deionized water, placed in a fume hood for natural drying, and ground to obtain a solid powder.
[0070] In some embodiments, the grinding is performed using an agate rock wall.
[0071] In step S02, the precursor powder is subjected to a two-stage sintering process to obtain a phosphate-based positive electrode material.
[0072] In some embodiments, a protective gas atmosphere is provided during the reaction. The main purpose of providing a protective gas atmosphere is to control the generation of no impurity molecules in the entire reaction environment, to ensure that there are no side reactions during the reaction process, and that no impurity molecules are generated. In some embodiments, the protective gas atmosphere includes, but is not limited to, a nitrogen atmosphere, an argon atmosphere, a helium atmosphere, and the like.
[0073] In some embodiments, the step of subjecting the precursor powder to a two-stage sintering treatment includes: heating the temperature from room temperature to 300-450°C at a heating rate of 2-15°C / min, maintaining for 3-6 hours, performing a first sintering treatment on the precursor powder, and then heating the temperature to 550-750°C at a heating rate of 2-15°C / min, maintaining for 4-8 hours, and performing a second sintering treatment.
[0074] The first sintering treatment is the pre-synthesis stage, which mainly uses low temperature and short time calcination conditions. This stage is mainly the nucleation process of phosphate-based cathode materials. The complete structure has not yet been formed, and the morphology of the particles is poor. The conditions for the first stage of sintering treatment are: use a heating rate of 2-15℃ / min from room temperature to 300-450℃, and maintain for 3-6h. At this stage, if the reaction temperature is too high or the reaction time is too long, side reactions will occur and impurities will be formed; if the reaction temperature is too low or the reaction time is too short, the reaction is insufficient, and it is impossible to fully react to form the lattice of the phosphate-based cathode material, and the lattice is unstable.
[0075] In some specific embodiments, in the first sintering treatment, the heating rate can be selected from typical but non-limiting arbitrary point values such as 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, or an interval value between any two point values; the heating temperature can be selected from typical but non-limiting arbitrary point values such as 300°C, 320°C, 350°C, 370°C, 400°C, 420°C, 450°C, or an interval value between any two point values; the heating time can be selected from typical but non-limiting arbitrary point values such as 3 hours, 4 hours, 5 hours, 6 hours, or an interval value between any two point values.
[0076] The second sintering treatment is the process of crystal nucleus growth. The particles of the phosphate-based positive electrode material are further grown in this process to obtain particles. The conditions of the second sintering treatment are to increase the temperature to 550-750°C at a rate of 2-15°C / min and maintain it for 4-8 hours. If the reaction temperature is too high or the reaction time is too long, the particles will grow too large, affecting the capacity of the material; if the reaction temperature is too low or the reaction time is too short, the particles will not grow sufficiently, and the properties of the finished particles will be poor.
[0077] In some specific embodiments, in the second sintering treatment, the heating rate can be selected from typical but non-limiting arbitrary point values such as 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, or an interval value between any two point values; the heating temperature can be selected from typical but non-limiting arbitrary point values such as 550°C, 570°C, 600°C, 620°C, 650°C, 680°C, 700°C, 720°C, 750°C, or an interval value between any two point values; the heating time can be selected from typical but non-limiting arbitrary point values such as 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, or an interval value between any two point values.
[0078] In some embodiments, after the first sintering process of the two-stage sintering process, a supplementary carbon material is added, and then the second sintering process of the two-stage sintering process is performed. In the specific reaction process, the chelated organic carbon material is added as a raw material, and after the first sintering process, the carbon content in the semi-finished product needs to be determined to ensure that the carbon content in the final product is 1.2% to 1.4%. If the carbon content in the final product is estimated to be less than 1.2%, it is necessary to add supplementary carbon material before performing the second sintering process.
[0079] In some embodiments, the supplementary carbon material can be selected from at least one of glucose, PEG-4000, and sucrose.
[0080] A third aspect of an embodiment of the present application provides a positive electrode plate, which includes a current collector and a positive electrode active layer formed on the surface of the current collector, and the positive electrode active layer includes the above-mentioned phosphate-based positive electrode material or a phosphate-based positive electrode material prepared by the above-mentioned method for preparing the phosphate-based positive electrode material.
[0081] The positive electrode plate provided in the third aspect of the embodiment of the present application has a positive electrode active layer including the above-mentioned phosphate-based positive electrode material with high conductivity and high compaction density. Therefore, the obtained positive electrode plate has high rate performance and can be widely used in various types of secondary batteries.
[0082] In some specific embodiments, the preparation method of the positive electrode sheet includes the following steps: mixing a composite phosphate-based positive electrode material, a conductive agent and a binder to obtain a mixed slurry; coating the mixed slurry on the surface of the current collector, and then performing post-processing such as drying, rolling, and die cutting to obtain a positive electrode sheet.
[0083] In some embodiments, the total mass of the positive electrode active layer is 100%, and the composite phosphate positive electrode material accounts for 90wt% to 95wt% of the total mass of the positive electrode active layer. The content of the composite phosphate positive electrode material can be 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, etc., which are typical but not limiting contents.
[0084] In some embodiments, the total mass of the positive electrode active layer is 100%, and the conductive agent accounts for 1wt% to 5wt% of the total mass of the positive electrode active layer. The content of the conductive agent can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, etc., which are typical but not limiting contents. The conductive agent is selected from at least one of graphite, carbon black, acetylene black, graphene, carbon fiber and carbon nanotubes.
[0085] In some embodiments, the total mass of the positive electrode active layer is 100%, and the binder accounts for 1wt% to 5wt% of the total mass of the positive electrode active layer. The content of the binder can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt% and other typical but non-limiting contents. Among them, the binder is selected from at least one of polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, 25 acrylonitrile copolymer, sodium alginate, chitosan, and chitosan derivatives.
[0086] Furthermore, the current collector includes but is not limited to any one of copper foil and aluminum foil.
[0087] A fourth aspect of an embodiment of the present application provides a secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is selected from the above-mentioned positive electrode sheets.
[0088] The secondary battery provided in the fourth aspect of the embodiment of the present application includes the above-mentioned positive electrode plate with high rate performance. Therefore, the obtained secondary battery has high cycle efficiency and high charge and discharge specific capacity.
[0089] The following describes the invention in conjunction with specific embodiments.
[0090] Example 1
[0091] A phosphate-based positive electrode material, the preparation method of which comprises the following steps:
[0092] (1) Take 74.6 mg of lithium carbonate, 96.8 mg of ferric nitrate, 125.2 mg of manganese nitrate, 115.1 mg of ammonium dihydrogen phosphate, 146.2 mg of ethylenediaminetetraacetic acid and 25 mL of deionized water, mix the above drugs evenly, and add the obtained mixed slurry into a 50 mL stainless steel hydrothermal kettle lined with polytetrafluoroethylene. After sealing the hydrothermal kettle, transfer it to a 180°C forced air drying oven for reaction for 12 hours. After the reaction is completed, the stainless steel reactor is removed from the forced air drying oven and naturally cooled to room temperature. The cooled reaction solution is filtered using a Buchner funnel, washed three times with 25 mL of deionized water, and the filter cake is placed in a fume hood and dried naturally to obtain a block solid. The obtained solid is ground into powder using an agate mortar to obtain a precursor powder.
[0093] (2) Sintering the powdered precursor in a nitrogen atmosphere; wherein the sintering is divided into a first sintering stage and a second sintering stage; the first sintering stage is to increase the temperature from room temperature to 300°C at a heating rate of 5°C / min and sinter for 4 hours; the second sintering stage is to increase the temperature from 300°C to 750°C at a heating rate of 5°C / min and sinter for 6 hours; and then cool the temperature from 750°C to room temperature at a cooling rate of 2°C / min to obtain a lithium manganese iron phosphate positive electrode material.
[0094] Example 2
[0095] A phosphate-based positive electrode material, the preparation method of which comprises the following steps:
[0096] (1) Take 30.4 mg of lithium hydroxide, 160.8 mg of iron sulfate, 90.6 mg of manganese sulfate, 115.1 mg of ammonium dihydrogen phosphate, 146.2 mg of sodium gluconate and 25 mL of deionized water, mix the above drugs evenly, and add the obtained mixed slurry into a 50 mL stainless steel hydrothermal kettle lined with polytetrafluoroethylene. After sealing the hydrothermal kettle, transfer it to a 150°C forced air drying oven for reaction for 6 hours. After the reaction is completed, the stainless steel reactor is removed from the forced air drying oven and naturally cooled to room temperature. The cooled reaction solution is filtered using a Buchner funnel, washed three times with 25 mL of deionized water, and the filter cake is placed in a fume hood and dried naturally to obtain a block solid. The obtained solid is ground into powder using an agate mortar to obtain a precursor powder.
[0097] (2) Sintering the powdered precursor in a nitrogen atmosphere; wherein the sintering is divided into a first sintering stage and a second sintering stage; the first sintering stage is to increase the temperature from room temperature to 300°C at a heating rate of 2°C / min and sinter for 3 hours; the second sintering stage is to increase the temperature from 300°C to 550°C at a heating rate of 2°C / min and sinter for 4 hours; and then cool the temperature from 550°C to room temperature at a cooling rate of 2°C / min to obtain a lithium manganese iron phosphate positive electrode material.
[0098] Example 3
[0099] A phosphate-based positive electrode material, the preparation method of which comprises the following steps:
[0100] (1) Take 74.6 mg of lithium carbonate, 96.8 mg of ferric nitrate, 125.2 mg of manganese nitrate, 115.1 mg of ammonium dihydrogen phosphate, 125.2 mg of polyacrylic acid and 25 mL of deionized water, mix the above chemicals evenly, and add the obtained mixed slurry into a 50 mL stainless steel hydrothermal kettle lined with polytetrafluoroethylene. After sealing the hydrothermal kettle, transfer it to a 200°C forced air drying oven for reaction for 24 hours. After the reaction is completed, the stainless steel reactor is removed from the forced air drying oven and naturally cooled to room temperature. The cooled reaction solution is filtered using a Buchner funnel, washed three times with 25 mL of deionized water, and the filter cake is placed in a fume hood and dried naturally to obtain a block solid. The obtained solid is ground into powder using an agate mortar to obtain a precursor powder.
[0101] (2) Sintering the powdered precursor in a nitrogen atmosphere; wherein the sintering is divided into a first sintering stage and a second sintering stage; the first sintering stage is to increase the temperature from room temperature to 450°C at a heating rate of 15°C / min and sinter for 6 hours; the second sintering stage is to increase the temperature from 450°C to 750°C at a heating rate of 15°C / min and sinter for 8 hours; and then cool the temperature from 750°C to room temperature at a cooling rate of 2°C / min to obtain a lithium manganese iron phosphate positive electrode material.
[0102] Comparative Example 1
[0103] A lithium manganese iron phosphate material, the specific operation steps are as follows:
[0104] (1) Take 74.6 mg of lithium carbonate, 96.8 mg of ferric nitrate, 125.2 mg of manganese nitrate, and 115.1 mg of ammonium dihydrogen phosphate, mix the above drugs evenly to obtain a mixture, and add the obtained mixed slurry into a 50 mL stainless steel hydrothermal kettle lined with polytetrafluoroethylene, seal the hydrothermal kettle and transfer it to a 180°C forced air drying oven for reaction for 12 hours. After the reaction is completed, the stainless steel reactor is removed from the forced air drying oven and naturally cooled to room temperature. The cooled reaction solution is filtered using a Buchner funnel, washed three times with 25 mL of deionized water, and the filter cake is placed in a fume hood and dried naturally to obtain a block solid. The obtained solid is ground into powder using an agate mortar to obtain a precursor powder.
[0105] (2) Sintering the mixture under a nitrogen atmosphere; wherein the sintering is divided into a first sintering stage and a second sintering stage; the first sintering stage is to increase the temperature from room temperature to 350°C at a heating rate of 5°C / min and sinter for 4 hours; the second sintering stage is to increase the temperature from 350°C to 750°C at a heating rate of 5°C / min and sinter for 6 hours; and then cool the temperature from 750°C to room temperature at a cooling rate of 2°C / min to obtain a lithium manganese iron phosphate positive electrode material.
[0106] Comparative Example 2
[0107] A lithium manganese iron phosphate material, the specific operation steps are as follows:
[0108] (1) Take 74.6 mg of lithium carbonate, 96.8 mg of ferric nitrate, 125.2 mg of manganese nitrate, 115.1 mg of ammonium dihydrogen phosphate, 146.2 mg of ethylenediaminetetraacetic acid and 25 mL of deionized water, mix the above drugs evenly, and add the obtained mixed slurry into a 50 mL stainless steel hydrothermal kettle lined with polytetrafluoroethylene. After sealing the hydrothermal kettle, transfer it to a 180°C forced air drying oven to react for 12 hours. After the reaction is completed, the stainless steel reactor is removed from the forced air drying oven and naturally cooled to room temperature. The cooled reaction solution is filtered using a Buchner funnel, washed three times with 25 mL of deionized water, and the filter cake is placed in a fume hood and dried naturally to obtain a block solid. The obtained solid is ground into powder using an agate mortar to obtain a precursor powder.
[0109] (2) Sintering the powdered precursor in a nitrogen atmosphere; wherein the sintering is divided into a first sintering stage and a second sintering stage; the first sintering stage is to increase the temperature from room temperature to 550°C at a heating rate of 5°C / min and sinter for 4 hours; the second sintering stage is to increase the temperature from 550°C to 750°C at a heating rate of 5°C / min and sinter for 6 hours; and then cool the temperature from 750°C to room temperature at a cooling rate of 2°C / min to obtain a lithium manganese iron phosphate positive electrode material.
[0110] Performance Testing
[0111] (I) The materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were subjected to morphological analysis, D 50 Particle size analysis, compaction density analysis, carbon content analysis, specific surface area analysis, resistivity analysis, and lithium ion diffusion coefficient analysis.
[0112] (ii) The materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were used as positive electrode materials for distribution and assembly to obtain secondary batteries, and the electrochemical performance of the obtained secondary batteries was tested under the conditions of 0.1C, 1C, 5C, and 10C, respectively.
[0113] (III) The finished materials obtained in Example 1, Comparative Example 1 and Comparative Example 2 were analyzed by scanning electron microscope.
[0114] Results Analysis
[0115] (I) The materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were subjected to morphological analysis, D 50 Particle size analysis, compaction density analysis, carbon content analysis, specific surface area analysis, resistivity analysis, and lithium ion diffusion coefficient analysis. The test results are shown in Table 1.
[0116] Table 1
[0117]
[0118] It can be seen that the morphology of the positive electrode materials obtained in Examples 1 to 3 is a secondary spherical shape, and D 50 Particle size>2.10μm, compacted density>2.4g / cm 3 , carbon content is 1.20~1.24%, specific surface area>12.68m 2 / g, resistivity <16.80Ω·m, diffusion coefficient of lithium ions >9.2×10 -13 cm 2 / S; while the morphology of the positive electrode material obtained in Comparative Example 1 is irregular large particles, and D 50 The particle size is only 1.49μm and the compacted density is only 2.289g / cm 3 , carbon content is 1.11%, specific surface area is 10.86m 2 / g, the resistivity is relatively large, which is 36.8Ω·m, and the diffusion coefficient of lithium ions is 6.8×10 -13 cm 2 / S; The morphology of the positive electrode material obtained in Comparative Example 2 is a mixture of large and small particles, and D 50 The particle size is only 1.78μm and the compacted density is only 2.325g / cm 3 , carbon content is 1.2%, specific surface area is 11.54m2 / g, but the resistivity is relatively high, which is 20.70Ω·m, and the diffusion coefficient of lithium ions is relatively low, which is 7.8×10 -13 cm 2 / S; It can be seen that the lithium iron phosphate positive electrode material prepared by the preparation method provided by the present invention has a regular morphology, a high compaction density, a low resistivity, a high diffusion coefficient of lithium ions, and excellent electrochemical performance.
[0119] In Comparative Example 1, a chelated organic carbon source is not used, but other materials are added, and no hydrothermal reaction is used. Therefore, direct sintering treatment will form large particles, and the carbon source coating effect of the non-metallic chelating agent is poor, which will cause small particles to sinter into large particles with irregular shapes. Although the material compaction in Comparative Example 2 is improved, during the two sintering processes, the method of first low-temperature sintering and then high-temperature sintering is not used, and direct high-temperature sintering is performed, resulting in the chelated organic carbon source being extracted and carbonized, and failing to form particles that can be agglomerated into large particles; resulting in the formation of a mixture of large and small particles.
[0120] (II) The materials obtained in Examples 1 to 3 and Comparative Examples 1 to 2 were used as positive electrode materials for distribution and assembly to obtain secondary batteries. The electrochemical performance of the obtained secondary batteries was tested at 25° C., 0.1C, 1C, 5C, and 10C. The specific results are shown in Table 2.
[0121] Table 2
[0122]
[0123] It can be seen from Table 2 that the secondary battery prepared by using the positive electrode materials obtained in Examples 1 to 3 has a charge / discharge capacity of ≥150 mA h / g at 0.1C, a discharge capacity of ≥139 mA h / g at 1C, a discharge capacity of ≥120 mA h / g at 5C, and a discharge capacity of ≥110 mA h / g at 10C, while the secondary battery prepared by using the positive electrode materials obtained in Comparative Examples 1 to 2 has a charge capacity of ≥150 mAh / g at 0.1C, a discharge capacity of <150 mA h / g, a discharge capacity of ≤137.6 mA h / g at 1C, a discharge capacity of ≤116.1 mA h / g at 5C, and a discharge capacity of ≤108.2 mA h / g at 10C; it can be seen that the secondary battery prepared by using the positive electrode materials obtained in Examples 1 to 3 has better electrochemical performance, and Comparative Example 2 belongs to the particle grading method, that is, the compaction density is increased by generating larger particles, resulting in that the electrochemical performance of the large particles is difficult to exert and the electrochemical properties are poor.
[0124] (III) The finished materials obtained in Example 1, Comparative Example 1 and Comparative Example 2 were analyzed by scanning electron microscope.
[0125] Figure 1The following are scanning electron microscope (SEM) images of the finished lithium manganese iron phosphate positive electrode material obtained in Example 1 at different magnifications. Figure 1 As can be seen in (a), the overall particles present a regular spherical nanoparticle shape, and the diameter of the spherical particles is 200-400nm. In the figure, the particles are closely adjacent to each other, and the surface of the particles is coated with a large amount of flocculent carbon. This carbon layer allows the small particles to maintain their original size under high-temperature calcination. Figure 1 (b) is a low-magnification SEM image, in which some small particles are aggregated into solid secondary particles of 5μm, and the remaining nanoparticles can be used as fillers to fill the gaps between the secondary particles, so as to achieve the purpose of improving the compaction density by one-step particle grading. There are no large-sized lithium manganese iron phosphate primary particles in the SEM image, so this method of increasing the compaction density will not affect the release of the electrochemical properties of the material.
[0126] Figure 2 The following are scanning electron microscope (SEM) images of the finished lithium manganese iron phosphate cathode material obtained in Comparative Example 1 at different magnifications. Figure 2 As can be seen from (a), the overall particles appear as irregular large particles.
[0127] Figure 3 The scanning electron microscope (SEM) images of different magnifications of the finished lithium manganese iron phosphate positive electrode material prepared in Comparative Example 2 are shown. It can be seen that the overall particles are a mixture of large particles and small particles.
[0128] In summary, the phosphate-based positive electrode material provided by the present application comprises a phosphate-based core and a carbon coating layer, wherein the provided carbon coating layer comprises a flocculent carbon coating layer, the flocculent carbon coating layer can reduce the resistivity and play a role in avoiding the risk of fusion and growth into large particles during high-temperature sintering, wherein the flocculent carbon coating layer is prepared from a chelated organic carbon material, and the chelated organic carbon material can also anchor the metals during the preparation process to avoid the generation of impurities, thereby ensuring the formation of highly crystallized, neatly shaped, uniform nano-sized grains, and the nano-scale particles are tightly agglomerated, which is beneficial to improving the overall compaction density of the material, and the carbon material can form a conductive network to improve the overall electronic conductivity of the material. Therefore, the obtained phosphate-based positive electrode material has a high compaction density and a large volumetric capacity, while meeting the requirements of high rate, high stability and high conductivity.
[0129] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A phosphate-based positive electrode material, characterized in that: The phosphate-based positive electrode material comprises a phosphate-based core and a carbon coating layer, wherein the carbon coating layer comprises a flocculent carbon coating layer, and the flocculent carbon coating layer is prepared from a chelated organic carbon material.
2. The phosphate-based positive electrode material according to claim 1, characterized in that: The phosphate-based positive electrode material is a micron secondary particle formed by agglomeration of several spherical nano primary particles, wherein the particle size of the primary particles is 200 to 400 nm, and the particle size of the secondary particles is 50 >5μm; and / or, The carbon coating layer also includes a common carbon layer.
3. The phosphate-based positive electrode material according to claim 1, characterized in that: Taking the total mass of the phosphate-based positive electrode material as 100%, the carbon content in the phosphate-based positive electrode material is 1.2% to 1.4%; and / or, The chemical formula of the phosphate core is LiM a Fe b Mn c PO4, wherein 0≤a≤0.05, 0.2≤b≤0.8, 0.2≤c≤0.8, and a+b+c=1; M is selected from at least one of Ti, Mg, V, Ni, Nb, Co, La, Sc, and Ce.
4. A method for preparing a phosphate-based positive electrode material, characterized in that: The steps include: A lithium source, an iron source, a manganese source, a phosphorus source, an M source and a chelated organic carbon material are mixed for hydrothermal reaction, and then post-processed to obtain a precursor powder; The precursor powder is subjected to a two-stage sintering process to obtain a phosphate-based positive electrode material.
5. The method for preparing a phosphate-based positive electrode material according to claim 4, characterized in that: The temperature of the hydrothermal reaction is 150-200°C and the time is 6-24 hours; and / or, The post-treatment comprises: cooling the mixture obtained by the hydrothermal reaction, filtering to obtain a precipitate, and washing, drying and grinding in sequence.
6. The method for preparing a phosphate-based positive electrode material according to claim 4, characterized in that: The step of subjecting the precursor powder to a two-stage sintering treatment comprises: heating the temperature from room temperature to 300-450°C at a rate of 2-15°C / min, maintaining the temperature for 3-6 hours, subjecting the precursor powder to a first sintering treatment, and then heating the temperature to 550-750°C at a rate of 2-15°C / min, maintaining the temperature for 4-8 hours, subjecting the precursor powder to a second sintering treatment; and / or, After the first sintering process of the two-stage sintering process, a supplementary carbon material is added, and then the second sintering process of the two-stage sintering process is performed.
7. The method for preparing a phosphate-based positive electrode material according to claim 4, characterized in that: The molar ratio of the lithium source, iron source, manganese source, phosphorus source and M source is 1.00-1.02: 0.2-0.8: 0.2-0.8: 1: 0-0.05; and / or, Taking the total mass of the raw materials as 100wt%, the added amount of the chelated organic carbon material is 0.1wt% to 10wt%.
8. The method for preparing a phosphate-based positive electrode material according to claim 4, characterized in that: The M source includes an oxide containing at least one element of Ti, Mg, V, Ni, Nb, Co, La, Sc, and Ce; and / or, The chelated organic carbon material includes at least one of diethanolamine, ethylenediaminetetraacetic acid, sodium gluconate, tartaric acid, and polyacrylic acid; and / or, The lithium source includes at least one of Li2CO3, LiH2PO4, LiOH·H2O, CH3COOLi, and LiNO3; and / or, The iron source includes at least one of Fe(NO3)3, Fe2O3, and FeSO4·7H2O; and / or, The manganese source includes at least one of Mn(NO3)3, Mn2O3, and MnSO4·7H2O; and / or, The phosphorus source includes at least one of (NH4)3PO4, NH4H2PO4, LiH2PO4, and H3PO4.
9. A positive electrode sheet, characterized in that: The positive electrode sheet includes a current collector and a positive electrode active layer formed on the surface of the current collector, and the positive electrode active layer includes the phosphate-based positive electrode material described in any one of claims 1 to 3 or the phosphate-based positive electrode material prepared by the method for preparing the phosphate-based positive electrode material described in any one of claims 4 to 8.
10. A secondary battery, characterized in that: The secondary battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is selected from the positive electrode sheet according to claim 9.